Aplicação do correntômetro acústico ADCP em ambientes marinhos e estuarinos do Ceará e Paraíba - Nordeste do Brasil - Bensi, Manuel (2006)
The knowledge of the agents acting on coastal dynamics is very important for the management and the adequate use of the littoral zone. The ADCP is an instrument that was using successfuly since some years (decade of ’80) for water current measurements in ocean and estuarine areas. In this work, the ADCP was aplicated in coastal areas ( between Fortaleza and Pecém) and two estaurine areas, in the Jaguaribe river (Cearà State) and Mamanguape river (Paraíba State). In the metropolitan region of Fortaleza, the two current surveys made in two different periods, showed a flux directed to the beach in May 2005, and a flux parallel to the littoral in July 2005. In Pecém currents measurements showed the protection effect of the harbour, where current speed was between 0,04 and 0,15 m/s, while offshore it was between 0,17 and 0,41 m/s. The ADCP use in estuarine zone, showed the estratification of Mamanguape river, and allowed a comparation between vertical current profile of salt wedge and well mixture estuaries.